Impact of Graft-Resident Leucocytes on Treg Mediated Skin Graft Survival - Steiner, Romy; Weijler, Anna M.; Wekerle, Thomas; Sprent, Jonathan; Pilat, Nina (Frontiers in Immunology, 2021)
The importance and exact role of graft-resident leucocytes (also referred to as passenger leucocytes) in transplantation is controversial as these cells have been reported to either initiate or retard graft rejection. T cell activation to allografts is mediated via recognition of intact or processed donor MHC molecules on antigen-presenting cells (APC) as well as through interaction with donor-derived extracellular vesicles. Reduction of graft-resident leucocytes before transplantation is a well-known approach for prolonging organ survival without interfering with the recipient’s immune system. As previously shown by our group, injecting mice with IL-2/anti-IL-2 complexes (IL-2cplx) to augment expansion of CD4 T regulatory cells (Tregs) induces tolerance towards islet allografts, and also to skin allografts when IL-2cplx treatment is supplemented with rapamycin and a short-term treatment of anti-IL-6. In this study, we investigated the mechanisms by which graft-resident leucocytes impact graft survival by studying the combined effects of IL-2cplx-mediated Treg expansion and passenger leucocyte depletion. For the latter, effective depletion of APC and T cells within the graft was induced by prior total body irradiation (TBI) of the graft donor. Surprisingly, substantial depletion of donor-derived leucocytes by TBI did not prolong graft survival in naïve mice, although it did result in augmented recipient leucocyte graft infiltration, presumably through irradiation-induced nonspecific inflammation. Notably, treatment with the IL-2cplx protocol prevented early inflammation of irradiated grafts, which correlated with an influx of Tregs into the grafts. This finding suggested there might be a synergistic effect of Treg expansion and graft-resident leucocyte depletion. In support of this idea, significant prolongation of skin graft survival was achieved if we combined graft-resident leucocyte depletion with the IL-2cplx protocol; this finding correlated along with a progressive shift in the composition of T cells subsets in the grafts towards a more tolerogenic environment. Donor-specific humoral responses remained unchanged, indicating minor importance of graft-resident leucocytes in anti-donor antibody development. These results demonstrate the importance of donor-derived leucocytes as well as Tregs in allograft survival, which might give rise to new clinical approaches.